Makna Simbolis dalam Kesenian Goong Renteng Sumedang: Kajian Etnografis pada Tradisi Musik Sunda: Makna Simbolis dalam Kesenian Goong Renteng Sumedang: Kajian Etnografis pada Tradisi Musik Sunda - Ruchimat, Hilal Hadyan; Ruchimat , Ismet (Awilaras, 2024)
Goong Renteng is a cultural heritage of the Sundanese people that is rich in philosophical values, especially those reflected in the concept of "silih asah, silih asih, silih asuh." This study aims to examine the philosophical and symbolic meanings of Goong Renteng, a traditional musical instrument from Sumedang, West Java, through a literature review. The research analyzes various sources, including books, scholarly articles, and previous studies, to explore how the structure, function, and use of Goong Renteng reflect the Sundanese worldview on togetherness, harmony, and the relationship between humans and nature. The findings indicate that Goong Renteng serves not only as a musical instrument but also as a symbol of local harmony and wisdom that must be preserved. Additionally, the study highlights the relevance of the values embedded in Goong Renteng in modern life, particularly in maintaining social and ecological balance. It is hoped that this research will contribute to the preservation of Sundanese culture and enrich the understanding of Indonesia'scultural heritage.